Settlement length and temporal settlement patterns of juvenile cod (Gadus morhua), haddock (Melanogrammus aeglefinus), and whiting (Merlangius merlangus) in a northern North Sea coastal nursery area - Bastrikin, Dorota K.; Gallego, Alejandro; Millar, Colin P.; Priede, Imants G.; Jones, Emma G. (ICES Journal of Marine Science, 2014)
Knowledge of settlement timing and duration, which has been identified as an important milestone for demersal fish, is critical to understanding population connectivity, relevant to the development of spatially—and temporally—resolved conservation measures, and recruitment variability, as important density-dependent dynamics may take place at this stage. To study the settlement ecology of cod haddock, and whiting, sampling was conducted over spring and summer 2004–2006 at the northern North Sea nursery area. Over 4000 0-group juveniles were collected. Settlement was associated with clear and progressive changes in the prey composition of these juveniles. The size of fish that could be considered settled was estimated as 49 (±3) mm for cod, 78 (±4) mm for haddock, and 85 (±6) mm for whiting. Clear differences in temporal settlement patterns were also apparent. Cod settled in a single pulse lasting about a month (mid-May to mid-June) and initially occupied shallower, inshore waters, whereas haddock settled in one pulse, lasting ∼2 weeks (second half of May), favouring deeper, farther offshore locations. Whiting settled much later in the season and over a more protracted period (early June to early August), and their depth preferences also changed over time and with increasing length.